The Shifting of Religiosity in the Area Affected by Steam Powered Electric Generator Batang Project - Fauyan, Muchamad (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2019)
This study aims to reveal religious attitude shifting of Ujungnegoro society as a village affected by the building of PLTU and its resolution. The method used was descriptive with study case technique. The data were collected through interviews, Focus Group Discussion, observation, and documentation. The qualitative analysis used Miles and Huberman Model. The shifting of religiosity of Ujungnegoro society was observed from 5 dimensions: Aqidah (creed), knowledge, ritual, religious practice, and appreciation. In the aspect of Aqidah, there is no change as new viewpoint appears. Knowledge dimension seemed increasing while others tended to decrease in quality. Spirituality and inner attitude of the society experienced inconvenience vis a vis modern lifestyle which is individualistic and materialistic. The shifting was influenced by the level of religious appreciation, family finance, and community environment factor applying consumptive and hedonistic culture. Negative effect of the building of PLTU on religious attitude was tackled by government figures, society, and religion through recitations and intense religious activities. However, those were not successful on increasing the societies spirituality, making simultaneous, systematic, systemic, and synergic da?wah with education technology approach through society?s literate improvement is needed which in turns is hoped to be followed by the bloom of inner spirituality.